Emotional exhaustion, academic self-efficacy, and academic procrastination as predictors of research motivation - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Castillo-Blanco, Ronald; Elguera Pajares, Ana; Lingan, Susana K. (Frontiers in Education, 2024)
Objective: To determine whether emotional exhaustion, academic self-efficacy, and academic procrastination predict research motivation in Peruvian university students.A cross-sectional predictive design was used and 1876 university students (59.9% female and 40.1% male), whose ages varied between 17 and 34 (M = 20.66; SD = 3.55), participated. The research motivation scale (RMS), academic self-efficacy scale (ASS), academic procrastination scale (APS), and the Single Item of Academic Emotional Exhaustion (SIAEE) scale were used to measure the variables.It is evident that the proposed model had an acceptable fit  2 (2) = 0.5, p = .784, comparative fit index = 1.000, root mean square error of approximation = .000, standardized residual root mean square = .003, showing that academic self-efficacy ( = .26, p < .001) and academic procrastination ( = −.26, p < .001) significantly predict research motivation, unlike emotional exhaustion, which does not predict research motivation ( = .03, p = .232).Academic self-efficacy and academic procrastination predict research motivation while emotional exhaustion does not, as reflected in the results.